Pond fish culture and needs for credit: A study in selected areas of Tangail district - Rahman, MA; Ahmed, F; Islam, MS; Khan, MA (Journal of the Bangladesh Agricultural University, 2016)
This study examines the cost, returns, profitability of pond fish farm, requirements, adequacy, sources and utilization patterns of credit and problems associated with pond fish farming in Madhupur Upazila of Tangail district. A total of 60 farmers with small traditional types of ponds were randomly selected for this study. Both description and econometric analysis were used. Human labour was the most important and one of the largest inputs used for pond fish production. The average per acre human labour cost, fingerlings cost, feed cost, chemical fertilizers cost, manure cost, and lime cost were Tk. 9345, Tk. 18506, Tk.10476, Tk.3759, Tk. 329, and Tk.1605, respectively. Pond rental value was calculated at Tk. 11537 per acre for one year which shared 26.42 percent of total costs of pond fish production. Gross return was Tk. 70928 per acre. Gross margin and net return of the pond fish farm were Tk.38118 and Tk. 24081 per acre respectively. The BCR was 1.514. Out of 60 farmers, only 11 farmers received loans from different sources and 86.67 percent of applied amount received. About 83 percent of the loan used for operating expenditure of farming and rest 17 percent loan used for non-farm expenditure. There were some problems in fish farming, such as insufficient water, high feed cost etc. Government needs to provide subsidized feed, technical supports and credit facilities for the small scale fish farmers. J. Bangladesh Agril. Univ. 13(1): 117-124, June 2015